Makna Ritual Kematian Bagi Warga Nahdlatul Ulama di Pragaan Laok Sumenep - Firdausi; Ahmad Shiddiq; Mohammad Affan Hidayatullah Amz (LPTNU Sumenep, 2024)
This research aims to discover the various forms, meanings and religious values contained in the death rituals of NU residents who have long existed in Pragaan Laok Village, Pragaan District, Sumenep. This ethnographic study uses natural seccing methods to understand the point of view of NU resident from a religious and traditional perspective. To find data, interviews, observation and documentation were used. Religious leaders, traditional leaders, village heads and NU residents were used as primary sources for gathering data. Once collected the data is analyzed through data reduction, categorization, synthesis and developing a working hypothesis. Next, check the validity of the data by extending participation, persistence of observation and triangulation. The research results concluded that are 21 death rituals. It’s just that some rituals have been abandoned by people who are literate in religious knowledge. The role of religious figures is being able to change some of these rituals by including Islamic, such as hanging the diamond above the door of funeral home, giving alms to the dead, praying, planting flowers for broken bones, sowing flowers and pouring water over graves. Thus, death rituals are local cultural products that were acculturated by the Wali Songo which are preserved, believed and sacred by the current generation. Because in this rituals there is meaning, philosophy and religious values from which NU resident should learn lessons. Even though millennials don’t know its meaning in depth, they still carry it out.